Experimental and numerical study of the effect of silica filler on the tensile strength of a 3D-printed particulate nanocomposite - Asif, Muhammad Usman; Ramezani, Maziar; Khan, Kamran Ahmed; Khan, Muhammad Ali; Aw, Kean Chin (Elsevier, 2019)
Polymers are commonly found to have low mechanical properties, e.g., low stiffness and low strength. To improve the mechanical properties of polymers, various types of fillers have been added. These fillers can be either micro- or nano-sized; however; nano-sized fillers are found to be more efficient in improving the mechanical properties than micro-sized fillers. In this research, we have analysed the mechanical behaviour of silica reinforced nanocomposites printed by using a new 5-axis photopolymer extrusion 3D printing technique. The printer has 3 translational axes and 2 rotational axes, which enables it to print free-standing objects. Since this is a new technique and in order to characterise the mechanical properties of the nanocomposites manufactured using this new technique, we carried out experimental and numerical analyses. We added a nano-sized silica filler to enhance the properties of a 3D printed photopolymer. Different concentrations of the filler were added and their effects on mechanical properties were studied by conducting uniaxial tensile tests. We observed an improvement in mechanical properties following the addition of the nano-sized filler. In order to observe the tensile strength, dog-bone samples using a new photopolymer extrusion printing technique were prepared. A viscoelastic model was developed and stress relaxation tests were conducted on the photopolymer in order to calibrate the viscoelastic parameters. The developed computational model of nano reinforced polymer composite takes into account the nanostructure and the dispersion of the nanoparticles. Hyper and viscoelastic phenomena was considered to validate and analyse the stress–strain relationship in the cases of filler concentrations of 8%, 9%, and 10%. In order to represent the nanostructure, a 3D representative volume element (RVE) was utilized and subsequent simulations were run in the commercial finite element package ABAQUS. The results acquired in this study could lead to a better understanding of the mechanical characteristics of the nanoparticle reinforced composite, manufactured using a new photopolymer extrusion 5-axis 3D printing technique.
Keywords: 3D printing; Hyperelastic; Photopolymer extrusion; Viscoelastic